Effect of cue validity on the contextual cueing effect - Su, Wen; Zhao, Guang; Ma, Jie (Frontiers in Psychology, 2024)
Purpose: In daily life, people are adept at extracting task-relevant information from complex visual environment to guide attention more effectively toward the target. This process underpins the contextual cueing effect, where repeated exposure allows individuals to learn associations between contextual cues and targets, thereby enhancing visual search efficiency. However, the cue validity of context -how consistently cues predict target locations-is not always guaranteed in real life. This study focused on cue validity as a critical factor in understanding the contextual cueing effect. Within the study of contextual cueing, cue validity specifically refers to the probability that contextual cues accurately indicate the location of a target.In Experiment 1, we manipulated three levels of cue validity (100%, 75%, and 50%) using a classic contextual cueing paradigm. Experiment 2 examined the potential impact of an imbalanced predictable vs. unpredictable trial ratio. In Experiment 3, we explored whether the absence of the contextual cueing effect was due to unsuccessful learning or unsuccessful later expression.Results: Results from Experiment 1 revealed that higher cue validity (100% and 75%) significantly elicited the contextual cueing effect, resulting in faster responses for repeated displays, whereas lower cue validity (50%) did not result in this effect because the repeated displays could not be effectively learned. Experiment 2 showed that the contextual cueing effect remained robust despite an imbalanced ratio of predictable to unpredictable displays. Experiment 3 further showed that low cue validity affects the early learning phase of context-target associations rather than the later expression in visual search.Our study highlights the significant role of cue validity in implicit learning from visual cues. High cue validity enhances learning by providing highly stable context-target associations, while low cue validity does not actively facilitate attention allocation, thereby not promoting the learning process. These findings underscore the importance of cue validity in processing visual information.